A case of traumatic duodenal perforation due to blunt abdominal trauma - Gadade, Gopal Diliprao; Borkar, Mrinalini; Sagrule, Dhiraj; Deo, Arpit; Shingade, Amarsingh (International Surgery Journal, 2022)
Duodenal injury following blunt abdominal trauma is a rare clinical entity and is often unnoticed leading to delay in management thereby increasing morbidity and mortality. We reported a case of duodenal perforation following blunt abdominal trauma with near complete transaction of duodenum at junction of D2 and D3 with grade 1 splenic laceration and highlight the challenges and decision-making dilemmas associated with its management.